Alkyl Passivation and Amphiphilic Polymer Coating of Silicon Nanocrystals for Diagnostic Imaging - Hessel, Colin M. (2010)
We show a method to produce biocompatible polymer-coated silicon (Si) nanocrystals for medical imaging. Silica-embedded Si nanocrystals are formed by HSQ thermolysis. The nanocrystals are then liberated from the oxide and terminated with Si-H bonds by HF etching, followed by alkyl monolayer passivation by thermal hydrosilylation. The Si nanocrystals have an average diameter of 2.1 ± 0.6 nm and photoluminesce (PL) with a peak emission wavelength of 650 nm, which lies within the transmission window of 650–900 nm that is useful for biological imaging. The hydrophobic Si nanocrystals are then coated with an amphiphilic polymer for dispersion in aqueous media with pH ranging between 7 and 10 and ionic strength between 30 mM and 2 M, while maintaining a bright and stable PL and a hydrodynamic radius of only 20 nm. Fluorescence imaging of polymer-coated Si nanocrystals in a biological tissue host is demonstrated, showing the potential for in vivo imaging.